2013
DOI: 10.4108/trans.amsys.01-06.2013.e4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive assessment of executive functions using brain computer interface and eye-tracking

Abstract: New technologies to enable augmentative and alternative communication in Amyotrophic Lateral Sclerosis (ALS) have been recently used in several studies. However, a comprehensive battery for cognitive assessment has not been implemented yet. Brain computer interfaces are innovative systems able to generate a control signal from brain responses conveying messages directly to a computer. Another available technology for communication purposes is the Eye-tracker system, that conveys messages from eye-movement to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Yet, as Mioshi et al have already described, neuropsychological abnormalities also occur in a very early stage of the disease and may even precede physical impairments [35]. Moreover, for completely locked-in state of ALS, the current study lacks the proof of applicability as correct eye movement control and the ability to blink in this state is not given by definition [14]. Then, additional Brain-Computer Interface technology is needed, which has recently been shown to be an effective means of communication in completely locked-in ALS patients [36].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Yet, as Mioshi et al have already described, neuropsychological abnormalities also occur in a very early stage of the disease and may even precede physical impairments [35]. Moreover, for completely locked-in state of ALS, the current study lacks the proof of applicability as correct eye movement control and the ability to blink in this state is not given by definition [14]. Then, additional Brain-Computer Interface technology is needed, which has recently been shown to be an effective means of communication in completely locked-in ALS patients [36].…”
Section: Discussionmentioning
confidence: 61%
“…By comparing classical paper-pencil and hand and speech motor-free oculomotor methods of neuropsychological tests, executive functions were determined using eye-tracking devices in ALS patients. Previous studies have shown the potential of oculomotor-based neuropsychological testing in healthy subjects [13,14]. We successfully demonstrated the usability of such approaches in a clinical context.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Even if the described protocol satisfies the need for a comprehensive evaluation of cognitive abilities, some issues arise from performing several tests with BCI; in particular, prolonged time for administration and cognitive effort could involve fatigue effects and reduce the reliability of the assessment. This study was included within an extended project, evaluating P300-BCI use for neuropsychological assessment with a particular attention to usability, pleasantness, fatigue, and emotional aspects [ 28 , 29 ]. Within such project, preliminary attempts to adapt another widely used traditional neuropsychological test, that is, Verbal Fluency, have been performed as a proof of concept which needs further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to cognitive assessment, the studies presented mainly employed ad hoc designed cognitive tasks, realized according to the characteristics and restrictions of the BCI paradigm adopted [ 21 , 22 , 25 , 30 ]. Cipresso et al [ 28 , 29 ] used a widely known cognitive test, that is, Verbal Fluency, even if with relevant modifications in administration and scoring methods with respect to the traditional “paper and pencil” version, in order to adapt to the BCI system. Differently, a few authors [ 23 , 24 , 27 ] realized a BCI-based version of a validated and standardized neuropsychological measure of fluid intelligence, that is, the RCPM, with particular attention at maintaining a reasonable adherence to the original test.…”
Section: Discussionmentioning
confidence: 99%